PENGARUH PARTISIPASI ANGGARAN, KEJELASAN SASARAN ANGGARAN DAN EVALUASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH (Studi Empiris pada SKPD Kota Pekanbaru) - Naipospos, Hevyana; Taufik, Taufeni; -, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to examine and analyze the effects of budget participation, budget goal clarity and budget evaluation againts the performance of local government apparatus in Pekanbaru city. The population in this research is local government apparatus is in SKPD (Service, Office, Agency) which includes 17 Service, 2 Offices and 7 Agencies, totally 26 units SKPD. The sampling technique using purposive sampling method. While the sample in this research is head of SKPD, head of planning and head of public and personnel, overall there are 3 respondents at each Service, Office and Agency. So the respondent in this research as many as 78 respondents. The data of this research using primary data directly through a questionnaire and analyzed using SPSS. The data were analyzed to test the hypothesis using multiple regression analysis approach. The results of this research that budget participation thitung>ttabel (2,164>1,994), budget goal clarity thitung>ttabel (3,552>1,994), and budget evaluation thitung>ttabel (3,811>1,994), affect the performance of local government apparatus.Keywords: Budget Participation, Budget Goal Clarity, Budget Evaluation, Performance Apparatus